Pemanfaatan Media Torso Plus untuk Meningkatkan Hasil Belajar Siswa SMPIT Al-Qalam Bengkulu Selatan - Zalna Fitri (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objective was to improve the eighth-grade students’ learning outcomes on Human Kinestic System through TORSO PLUS Media at SMPIT Al-Qalam South Bengkulu A classroom action research was implemented to all the eighth grade students in two cycles with its four phases, namely: planning,action,observation,refelection. Data were collected by means of two instruments, they are: a test on concept comprehension and observation checklist. Data were analyzed descriptively using mean scores for the students’ learning outcomes, observation and minimum mastery level.Analysis results show that the students’ learning outcomes improved from 75.07 with minimum mastery level = 56.67% in cycle 1. Whereas, their learning outcomes improved to = 89.07 with minimum mastery level = 86.67%. In general, TORSO PLUS media could improve the students’ learning outcomes as well as the minimum mastery levels SMPIT Al-Qalam South Bengkulu.